The results of treatment with high-dose chemotherapy and peripheral blood stem cell support for gestational trophoblastic neoplasia. (March 2019) - Frijstein, M.M.; Lok, C.A.R.; Short, D.; Singh, K.; Fisher, R.A.; Hancock, B.W.; Tidy, J.A.; Sarwar, N.; Kanfer, E.; Winter, M.C.; Savage, P.M.; Seckl, M.J.
Abstract: Objective: The objective of the study was to evaluate the effect of high-dose chemotherapy (HDC) with peripheral blood stem cell support (PBSCS) on survival of patients with gestational trophoblastic neoplasia (GTN) with either refractory choriocarcinomas or a poor-prognosis placental site/epithelioid trophoblastic tumours (PSTT/ETTs). Methods: Databases of two referral centres for gestational trophoblastic disease were searched, and 32 patients treated with HDC between 1994 and 2015 were identified. Tissue samples were retrieved for genetic evaluation. Cox regression analyses were performed to identify possible predictors of overall survival (OS). Results: HDC induced a sustained complete response in 7 patients. Overall, 41% (13/32) of the patients remained disease free after HDC with or without additional treatment. Patients who survived had much lower human chorionic gonadotropin (hCG) values (all ≤12 IU/L) before and after HDC than those who died of disease. Univariable Cox regression analysis demonstrated that hCG >12 IU/L before or after HDC, International Federation of Gynaecology and Obstetrics (FIGO) stage II-IV and presence of metastases at the time of diagnosis were significantly associated with adverse OS. However, only hCG values before HDC remained significant in a multivariable model ( p < 0.001). Five of 11 (45%) patients with PSTT/ETT presenting ≥48 months after antecedent pregnancy and 6 of 14 (43%) patients with refractory choriocarcinoma were in remission. Three treatment-related deaths occurred. Conclusions: Despite 3 treatment-induced deaths, HDC with PBSCS appears to be active in salvaging selected patients with poor-prognosis PSTT/ETTs and refractory choriocarcinomas. Low hCG values before HDC seems a beneficial predictor of OS and may suggest that HDC acts more like a consolidation therapy. Highlights: Low hCG levels before high-dose chemotherapy, a favourable prognostic factor. HDC appears to cure a subset of poor-prognosis placental site/epithelioid trophoblastic tumour patients. HDC can salvage a significant proportion of women with refractory choriocarcinoma.